Security in Computer and Information Sciences First International ISCIS Security Workshop 2018, Euro-CYBERSEC 2018, London, UK, February 26-27, 2018, Revised Selected Papers - Gelenbe, Erol; Campegiani, Paolo; Czachórski, Tadeusz; Katsikas, Sokratis K.; Komnios, Ioannis; Romano, Luigi; Tzovaras, Dimitrios (Communications in Computer and Information Science, 2018)
This open access book constitutes the thoroughly refereed proceedings of the First International ISCIS Security Workshop 2018, Euro-CYBERSEC 2018, held in London, UK, in February 2018. The 12 full papers presented together with an overview paper were carefully reviewed and selected from 31 submissions. Security of distributed interconnected systems, software systems, and the Internet of Things has become a crucial aspect of the performance of computer systems. The papers deal with these issues, with a specific focus on societally critical systems such as health informatics systems, the Internet of Things, energy systems, digital cities, digital economy, mobile networks, and the underlying physical and network infrastructures.